2017
DOI: 10.1002/bdra.23594
|View full text |Cite
|
Sign up to set email alerts
|

Association of essential trace metals in maternal hair with the risk of neural tube defects in offspring

Abstract: We concluded that maternal intakes of the four ETMs (Ni, Mo, Zn, and Sn) played an important role in the formation of NTDs in our study population, and that this intake is related to maternal dietary habits.Birth Defects Research 109:234-243, 2017.© 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 43 publications
1
16
1
Order By: Relevance
“…Our study is the first to evaluate Mo levels in amniotic fluid in pregnancies complicated with NTDs. Sn was studied for the first time by Yan et al, who suggested a possible protective effect of Sn on the NTD risk . Our results do not agree with their data in that we observed higher amniotic fluid levels of Sn in pregnancies complicated with NTDs.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Our study is the first to evaluate Mo levels in amniotic fluid in pregnancies complicated with NTDs. Sn was studied for the first time by Yan et al, who suggested a possible protective effect of Sn on the NTD risk . Our results do not agree with their data in that we observed higher amniotic fluid levels of Sn in pregnancies complicated with NTDs.…”
Section: Discussioncontrasting
confidence: 99%
“…Vazquez‐Salas et al reported a potential negative association between prenatal Mo exposure and infant neurodevelopment . On the contrary, in a study in 191 women with NTD‐affected pregnancies, Yan et al reported that a high Mo level in maternal hair was clearly a protective factor against either anencephaly or spina bifida . Our study is the first to evaluate Mo levels in amniotic fluid in pregnancies complicated with NTDs.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…S1). The epidemiology data highlight that lower zinc levels in maternal or fetal tissues are associated with NTDs in Turkey (Çavdar et al, 1991Cengiz et al, 2004;Demir et al, 2017;Zeyrek et al, 2009), Iran (Golalipour et al, 2009), China (Yan et al, 2017), Netherlands (Groenen et al, 2003), England (Buamah et al, 1984;Hinks et al, 1989;Leger et al, 1980), Bangladesh (Dey et al, 2010), Mexico (Carrillo-Ponce Mde et al, 2004) and India (Srinivas et al, 2001) (blue frames in Fig. S1).…”
Section: Introductionmentioning
confidence: 99%